COMMODITY ETFS IN THE JAPANESE STOCK EXCHANGES - Yamori, Nobuyoshi (Journal of Advanced Studies in Finance; Vol 2 No 1 (2011): JASF Volume II Issue 1(3) Summer 2011, 2011)
This paper analyzes commodity investment trusts and commodity ETFs as a method for investing in commodities, which are expected to be an important tool for individual investors to participate in commodity investments. The “Financial Big Bang” reforms during the latter half of the 1990s substantially transformed the Japanese financial system, which had been strictly regulated. Recently, thanks to financial deregulation, there are 30 commodity ETFs listed on the Tokyo Stock Exchange or the Osaka Securities Exchange. However, this paper finds that most of commodities ETFs are thinly traded. So, we need to implement further policy as soon as possible in order to encourage Japanese investors to participate in the commodity ETF market. Otherwise, investors will lose their interests in Japanese commodity ETF markets. Finally, this paper investigates whether new commodity ETFs compete against traditional commodity future markets. The paper finds that growing commodity ETFs increase transactions in traditional commodity futures markets, such as the Tokyo Commodity Exchange. Encouraging more commodity ETFs transaction may lead to active arbitrages between ETFs markets and commodity future markets. In sum, our results suggest that commodity ETFs are beneficial to traditional commodity future markets.